Unified Calculation Model and Its Verification of Gear Cross-section Area for Arbitrary Tooth Profile - Yulong Li; Jun Fan; Xiurong Li; Yong Zang (Jixie chuandong)
To derive a unified calculation model for gear cross-section area suitable for arbitrary tooth profile. Firstly， based on the external conjugate relation between two identical gear， it is analyzed that cross-section area of gear is composed of pitch circle area， plus conjugated area， and minus minimum top gap area. Secondly， based on the geometric relationship of conjugate profile， the simplest calculation formula without error of the conjugated area and simplified calculating method of minimum top gap area adopts partial hob are given. Finally， example calculation and analysis of gear cross-section area with involute profile are carried out. All results show that the pitch circle area is much larger than conjugated area and minimum top gap area， but calculation method of minimum top gap area determined calculation accuracy of cross-section area， the theory error of gear cross-section area is 0.24%，which could be used in high precision calculation of gear cross-section area. It is concluded that the conjugated area formula is suitable for volume utilization coefficient calculation in arbitrary tooth profile without error for pump.